USING AERIAL SURVEY OBSERVATIONS TO IDENTIFY WINTER HABITAT USE OF MOOSE IN NORTHERN MAINE - Andreozzi, Haley A.; Pekins, Peter J.; Kantar, Lee E. (Lakehead University, 2016)
Winter habitat use by moose (Alces alces) is typically comprised of regenerating forest and softwood cover in the northeastern United States, and globally, high winter densities are of concern relative to forest damage. Habitat variables associated with winter locations of moose collected during aerial surveys in Maine in 2011 and 2012 were compared to available habitat at multiple landscape scales. Mixed forest was the most used land cover type at both the location and 5 ha scales (35.1% and 31.3%, respectively). Although regenerating forest habitat was used only in proportion to availability, the proximity to recent clearcuts, light partial cuts, and heavy partial cuts was an important predictor of moose location. The used proportion of coarse habitat variables (i.e., mature and regenerating forest) were similar to those available in each aerial survey block, indicating that heterogeneous and productive moose habitat is widely available across the commercial forest landscape of northern Maine. Moose locations derived from aerial surveys can provide insight about spatial distribution and habitat use across the landscape, identify local density in areas where forest regeneration is of concern, and monitor population responses to commercial forest management practices.